Soil Application of a Formulated Biocontrol Rhizobacterium, Pseudomonas chlororaphis PCL1606, Induces Soil Suppressiveness by Impacting Specific Microbial Communities - Tienda, Sandra; Vida, Carmen; Lagendijk, Ellen; de Weert, Sandra; Linares, Irene; González-Fernández, Jorge; Guirado, Emilio; de Vicente, Antonio; Cazorla, Francisco M. (Frontiers in Microbiology, 2020)
Biocontrol bacteria can be used for plant protection against some plant diseases. Pseudomonas chlororaphis PCL1606 (PcPCL1606) is a model bacterium isolated from the avocado rhizosphere with strong antifungal antagonism mediated by the production of the compound 2-hexyl, 5-propil resorcinol (HPR). Additionally, PcPCL1606 has biological control against different soil-borne fungal pathogens, including Rosellinia necatrix, which causes the emerging white root rot disease of many woody crops, including avocado in the Mediterranean area. The objective of this study was to assess whether the semicommercial application of PcPCL1606 to soil can potentially affect avocado soil and rhizosphere microbial communities and their multiple functions in natural conditions and under R. necatrix infection. To test the potential effects of PcPCL1606 on soil eukaryotic and prokaryotic communities, a formulated PcPCL1606 was prepared and applied to the soil of avocado plants growing in mesocosm experiments, and the communities were analysed by using 16S/ITS metagenomics. PcPCL1606 survived until the end of the experiments. The effect of PcPCL1606 application on prokaryotic communities in soil and rhizosphere samples from natural soil was not detectable, and very minor changes were observed in eukaryotic communities. In the infested soils, the presence of R. necatrix strongly impacted the soil and rhizosphere microbial communities. However, after PcPCL1606 was applied to soil infested with R. necatrix, the prokaryotic community reacted by increasing the relative abundance of few families with protective features against fungal soilborne pathogens and organic matter decomposition (Chitinophagaceae, Cytophagaceae), but no new prokaryotic families were detected. The treatment of PcPCL1606 impacted the fungal profile, which strongly reduced the presence of R. necatrix in avocado soil and rhizosphere, minimizing its effect on the rest of the microbial communities. The bacterial treatment of formulated PcPCL1606 on avocado soils infested with R. necatrix resulted in biological control of the pathogen. This suppressiveness phenotype was analysed, and PcPCL1606 has a key role in suppressiveness induction; in addition, this phenotype was strongly dependent on the production of HPR.